2005
DOI: 10.1097/00042737-200503000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Thrombophilic gene mutations in cirrhotic patients with portal vein thrombosis

Abstract: Inherited thrombophilic gene mutations appear to increase the risk of PVT formation in cirrhotic patients but not in patients without liver disease in a cohort of Turkish patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 0 publications
2
36
2
1
Order By: Relevance
“…10,11 On the other hand, our study did not confirm either the increased frequency of prothrombin G20210A mutation in PVT or the suggestion that homozygous MTHFR C677T genotype is strongly associated with this medical entity. [12][13][14][15] Furthermore, we could not substantiate the results of other reports 16 concerning the role of LA in PVT, as LA was recovered neither in any PVT patient nor in any other of our patients. In our study, MPD as a cause of PVT ranked second (22.2%) after liver cirrhosis (33.3%), but most of the previous studies found them to prevail with prevalence rates ranging from 30% to 48%.…”
Section: Portal Vein Thrombosiscontrasting
confidence: 94%
“…10,11 On the other hand, our study did not confirm either the increased frequency of prothrombin G20210A mutation in PVT or the suggestion that homozygous MTHFR C677T genotype is strongly associated with this medical entity. [12][13][14][15] Furthermore, we could not substantiate the results of other reports 16 concerning the role of LA in PVT, as LA was recovered neither in any PVT patient nor in any other of our patients. In our study, MPD as a cause of PVT ranked second (22.2%) after liver cirrhosis (33.3%), but most of the previous studies found them to prevail with prevalence rates ranging from 30% to 48%.…”
Section: Portal Vein Thrombosiscontrasting
confidence: 94%
“…61 The frequency of Factor V Leiden mutation (29%) and prothrombin gene mutation (29%) are more frequent in cirrhosis with PVT compared to cirrhosis without PVT, non-cirrhotics with PVT and healthy controls. 62 …”
Section: Portal Vein Thrombosis In Cirrhosis Procoagulant Statementioning
confidence: 99%
“…En una serie de 92 pacientes con trombosis venosa portal sólo 3 pacientes (3,2%) tuvieron la mutación G20210A, mientras que en otra serie 14 (22%) de un total de 65 pacientes tuvieron la mutación G20210A (7,8). La trombosis venosa portal asociada a cirrosis hepática podría tener una etiopatogenia distinta, pero igualmente se han implicado mutaciones trombofílicas, como la mutación G20210A (9,10). La mutación G20210A también se ha descrito en la trombosis venosa mesentérica (11).…”
Section: Discussionunclassified